2021
DOI: 10.1186/s12885-021-08986-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum ferritin levels and malignant intraductal papillary mucinous neoplasms

Abstract: Background Serum ferritin levels are elevated in many malignancies. In this study, we showed the performance of serum ferritin in identifying malignant intraductal papillary mucinous neoplasms (IPMNs). Methods A total of 151 patients with pathologically confirmed IPMNs were enrolled. Serum tumor biomarker (carbohydrate antigen 19–9 (CA19–9) and carcinoembryonic antigen (CEA)) levels and serum ferritin levels were recorded. Lesion location, tumor si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A recent study indicates that mucin 5AC (MUC5AC) in a circulating extracellular vesicle can predict high-grade IPMNs with an AUC of 0.73 and predict invasive carcinoma with an AUC of 0.91 (32). Our previous study also reported that serum ferritin had acceptable performance (AUC = 0.67) (33). In the present study, our data further showed that the diagnostic power of PA alone was comparable to that of MPD or MN (AUC = 0.71) and the serum biomarkers of CA19-9 or serum ferritin or a circulating extracellular vesicle in identifying malignant IPMNs but lower than that of the circulating extracellular vesicle in identifying invasive carcinoma (32).…”
Section: Discussionmentioning
confidence: 75%
“…A recent study indicates that mucin 5AC (MUC5AC) in a circulating extracellular vesicle can predict high-grade IPMNs with an AUC of 0.73 and predict invasive carcinoma with an AUC of 0.91 (32). Our previous study also reported that serum ferritin had acceptable performance (AUC = 0.67) (33). In the present study, our data further showed that the diagnostic power of PA alone was comparable to that of MPD or MN (AUC = 0.71) and the serum biomarkers of CA19-9 or serum ferritin or a circulating extracellular vesicle in identifying malignant IPMNs but lower than that of the circulating extracellular vesicle in identifying invasive carcinoma (32).…”
Section: Discussionmentioning
confidence: 75%
“…[24] However, when iron stores are in excess, the free iron content increases, which can enhance the oxidative stress response of the body, leading to an increase in blood pressure and causing the development of hypertensive disorders during pregnancy. [25] Vitamin D levels are altered in pregnant women during pregnancy, and elevated maternal D25-(OH)-D concentrations, which are higher than those in the fetus, can be transported to the fetus through the placenta to replenish vitamin D levels in the fetus. [26] Reduced maternal D25-(OH)-D levels have been found to be correlated with the severity of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin was found to have similar predictivity as CA19-9 in assessing IPMN. As discussed above, when CA19-9 is elevated in cases of IMPN, while not diagnostic, it is another concerning data point when considering malignant risk [ 67 ].…”
Section: Inflammationmentioning
confidence: 99%